2019
DOI: 10.1177/0269216319830017
|View full text |Cite
|
Sign up to set email alerts
|

The experiences and needs of primary family caregivers of patients with multiple myeloma: A qualitative analysis

Abstract: Background: Family caregivers play a key role in the lives of patients with multiple myeloma. However, very little is known about the impact that the disease (its diagnosis, course and prognosis) has on the main family caregiver. Aim: To achieve a deeper understanding of the lived experience of individuals who are the primary caregiver of a relative with multiple myeloma and to shed light on their needs. Design: Interpretative phenomenological study. Setting and participants: A total of 12 individuals wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 35 publications
0
22
0
Order By: Relevance
“…In this study, researchers based the educational intervention and peer support, including the educational workshops, support group, and follow-up assessments on the detailed needs assessment to address the speci c needs of the family caregivers of leukemia patients. Accordingly, the results of the study of Quiñoa-Salanova et al, (2019) aiming at an understanding of the lived experience of the primary caregiver of a relative with multiple myeloma indicated that targeting psychological aspects of family caregivers' lives is hinged on the accurate assessment of the speci c needs of family caregivers [31]. Akyar et al, (2019) in their study with the view to planning a palliative care model for adaptation of Turkish family caregivers of older individuals with cancer maintained needs assessment should be the rst phase of planning for family caregivers of cancer patients [32].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, researchers based the educational intervention and peer support, including the educational workshops, support group, and follow-up assessments on the detailed needs assessment to address the speci c needs of the family caregivers of leukemia patients. Accordingly, the results of the study of Quiñoa-Salanova et al, (2019) aiming at an understanding of the lived experience of the primary caregiver of a relative with multiple myeloma indicated that targeting psychological aspects of family caregivers' lives is hinged on the accurate assessment of the speci c needs of family caregivers [31]. Akyar et al, (2019) in their study with the view to planning a palliative care model for adaptation of Turkish family caregivers of older individuals with cancer maintained needs assessment should be the rst phase of planning for family caregivers of cancer patients [32].…”
Section: Discussionmentioning
confidence: 99%
“…Gaining a greater understanding of family CGs' needs and experiences would enhance the overall process of caring for patients with HMs assisted at home. To our knowledge, very little information is available in the literature on CGs in home care settings [34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50], especially in advanced HMs. Although in several studies, CGs describe positive outcomes, such as feelings of privilege, accomplishment, and improved family relationships [34], other studies pointed out the heavy burden perceived by the CG and the physical and emotional exhaustion experienced especially at the end of life [35,37].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the most important issues are a lack of exhaustive communication between HPs and families [37], advice by HPs, support and training during home assistance [36], and an empathic attitude towards CGs [41]. Some studies report that CGs' expectations for support sometimes had apparently not been met by HPs and they felt themselves viewed as 'co-workers' instead of people with their own needs [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Caregivers have needs, doubts, and fears, which express uncertainties about the future in terms of patients' survival and quality of life (QoL), particularly fears of death and prolonged suffering (Beattie & Lebel, 2011;Quiñoa-Salanova, Porta-Sales, Monforte-Royo, & Edo-Gual, 2019). On top of these uncertainties, burden negatively influences caregivers' QoL (Grant et al, 2013;La & Yun, 2017;Lapid et al, 2016) insofar as it may affect caregivers' physical and psychological health, autonomy, and social relations (World Health Organization Quality of Life Group, 1994).…”
Section: Introductionmentioning
confidence: 99%